PLACENTA PREVIA IN PREGNANT WOMEN: EXPERIENCE OF CORRECTION OF THE CERVIX WITH THE DOMED ARABIN PESSARY, PLACENTAE ACCRETO PREDICTION - Сергей Владимирович Баринов; Юлия Игоревна Тирская; Татьяна Владимировна Кадцына; Оксана Вячеславовна Лазарева; Ирина Владимировна Медянникова; Ольга Юрьевна Атаманенко (The Publishing House Medicine and Enlightenment, 2021)
Anomalies in the location and attachment of the placenta are the main causes of maternal morbidity. Methods of diagnostics, algorithms for observation and delivery of women with this pathology have been developed, however, the issues of predicting an increase in placenta previa remain open and there are no methods of secondary prevention of this complication. The aim of the research - assessment of the role of cervical correction with the Arabin domed pessary on migration and augmentation of plasenta praevia, search for predictors of abnormal attachment of the placenta. Materials and methods. 120 pregnant women with placenta previa were examined. All pregnant women [group A (n = 60) and group B (n = 60)] received micronized progesterone 200 mg/day. In group A, an Arabin pessary was placed on the cervix at 18 weeks. Ultrasound was performed at 18, 24, 28, 33 weeks with IR measurement in the arcuate arteries of the placenta region. Results. With the use of the Arabin pessary, placental migration was observed twice as often. Placental migration was observed against the background of low-resistance blood flow in the arcuate arteries of the placental region. Placental accreta was observed in 26.2 % of cases in women with uterine scars and was associated with highly resistant blood flow. The use of a pessary reduced the incidence of placentae accreto by 1.3 times. The ROC analysis made it possible to identify predictors of placenta accreta: history of endometritis, anemia, Purselo index values in the arcuate arteries of the placenta region at 28 weeks above 0.69 and at 33 weeks above 0.73. Conclusion. Placenta previa is more often formed in women with a complicated obstetric history. 46 % have placental migration, more often along the anterior wall (62 %). The use of the Arabin pessary can reduce the risk of abnormal attachment of the placenta by 1.3 times. Predictors of an increase in placenta previa: a history of endometritis, anemia, the IR value in the arcuate arteries of the placenta region at 28 weeks is higher than 0.69, and at 33 weeks is higher than 0.73.